(untitled) (Biological Sciences - PJSIR, 2004)
Probiotics are viable bacteria used as feed additives, which produce beneficial effects that bring about a balance of the intestinal flora. Strains of Lactobacillus, Pediococcus, Bacteriodes, Bifido bacterium, Bacillus, Streptococcus and Escherichia coli have been used as probiotics (Fuller 1986).